Model Pengabdian Berbasis Inklusifitas Dan Berkelanjutan: Transformasi UMKM Perempuan Desa Dukuhdempok Melalui Program Promahadesa: Peran Program Promahadesa terhadap pelaku UMKM Kelompok Perempuan dalam Meningkatkan Kesejahteraan Masyarakat Desa Dukuhdempok - Chintya Dwi Lestari; Mohammad Taufiqur Rahman; Selvi Putri Ismania; Wahyu Deva Romadhon; Andjani Prasetya Dewi; Yunita Rizqi Hidayah; Muhammad Idham Arwani; Ayu Amilia (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2025)
Abstract: The Village Community Service Program (PROMAHADESA) is an initiative to empower groups of former migrant workers in Dukuh Dempok Village, Jember Regency, focusing on the development of Micro, Small, and Medium Enterprises (MSMEs) based on inclusivity and sustainability. This program is carried out through strategic collaboration with DESBUMI (Village Caring for Migrant Workers) as the main partner, and the Halal Center as the technical partner, with the primary goal of assisting MSME entrepreneurs in obtaining business legality, such as the Business Identification Number (NIB), Household Food Industry Production Certificate (SPP-IRT), and halal certification. This activity includes crucial stages, such as identifying data on MSME actors, socializing the importance of business legality, digital marketing training, and intensive assistance in the business licensing process. The highlight of the activity was marked by the handover of business legality certificates to 25 MSME actors, who now have a legal foundation for the development of their businesses. The program results show an increase in awareness and skills among MSME actors in managing their businesses professionally, expanding market access, and enhancing competitiveness in the digital era. This program not only contributes to economic transformation through business legality but also strengthens the role of women in sustainable inclusive development. With a needs-based approach and support from strategic partners, PROMAHADESA becomes a holistic, inclusive, and sustainable service model, providing real impact for village communities and supporting the achievement of sustainable development goals. Keywords: Dukuh Dempok, Inclusive, MSMEs